Hanseníase no município de Sobral, Ceará : análise epidemiológica e operacional das ações de eliminação no período de 1997 a 2003 - Campos, Sandra Solange Leite (2005)
In the last 20 years, Brazilian health policy has been provoking fruitful discussions on the decentralization of the primary health care system. Even in the 21st century, the implementation of leprosy control measures on the public health level has been an ongoing challenge. In this context, the Family Health Program is a strategy for the reorientation and restructuring of the unified health system. This study has the objective to describe the epidemiologic factors that influenced the process of integration of leprosy control measures in the primary health care system in the Municipality of Sobral from 1997 to 2003. Sobral has been selected, as it represents one of the prioritized Municipalities for leprosy control in Ceará and as it is an example of successful implementation of an effective primary health care system. The process of leprosy elimination in the primary health care of Sobral was analyzed based on a retrospective description in the period from 1997 to 2003. The analysis of the epidemiological and operational indicators favored by the National Program of Leprosy Elimination, revealed high detection rates, mainly in 2003. Besides, considerable inconsistencies in age, clinical forms and operational classification indicate the possibility of diagnostic errors. Finally, in this study the process of integration of leprosy control measures in the Municipality of Sobral has been related to the epidemiological indicators. The possibility to develop integrated health care for leprosy patients in the primary health care system with effective involvement and control of community associations and other nongovernmental organizations is emphasized. The need to evaluate and monitor the epidemiology of leprosy, even in situations in which control measures seem to be successful, as it is the case with Sobral, is also discussed.